Survey on educational material on sustainable constructions - Koukkari, Heli (2008)
Higher education of professionals in the construction and real estate sector is in the process of “Greening curricula”. Pressures to educate environmentally literate workforce are increasing. Leading construction companies worldwide are becoming involved in green construction. “Green building, green project, green property, green procurement as well as green living and green citizenship” are concepts that are used in business like in voluntary organisations. The literature survey shows that technical universities worldwide have incorporated modules, courses and programmes of sustainable construction. In general, new teaching methods and approaches are regarded as necessary due to the complexity of triple bottom-line issues of the sustainable construction. In addition to traditional lecturing and exercises, life-cycle and overall performance matters are taught by methods of team-work, problem-solving and learning- by-doing. The material for this study was gathered from literature and virtual site visits of universities as well as a questionnaire among the participants of the COST C25. First remarks concerning all the material is that there are still few technical universities with a cross-cutting strategy about sustainability. Among the participants of the C25, 50% informed about systematic educational approach. This study is related to the initiative in the WG2 of C25 to establish a knowledge base to support development of educational material on sustainable constructions.